How Should We Measure Body Temperature in the Pediatric Emergency Department? Which One Is the Most Accurate? - Türe, Esra; Yazar, Abdullah (Journal of Pediatric Infectious Diseases, 2019)
The aim of this study is to evaluate temperature measurement methods in children. Body temperatures of 3 to 18 years old patients were measured with a tympanic infrared thermometer, a noncontact infrared skin thermometer and with a temporal artery thermometer. While the specificity of temporal artery and noncontact thermometers were good in determination of temperatures above 37.5°C, their sensitivities were low. Positive predictive value and negative predictive value for both thermometers were sufficient. Both specificity and sensitivity of both thermometers were determined to be good at temperature values above ≥ 38°C. It is thought that noncontact and temporal artery thermometers can be used for screening in pediatric emergency departments.
Keywords: temporal artery thermometer; tympanic thermometer; noncontact infrared forehead thermometer; pediatrics; temperature measurement